PENGARUH GAYA KEPEMIMPINAN DAN PEMBERIAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT. BAGONG SANGATTA - Devi Ambarwati; Muhammad Andreas Y Sutrisno; Andi Mursalin (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2020)
To analyze the effect of leadership style and compensation on the performance of employees of PT Bagong Sangatta. This research method is a quantitative research. The population is 80 employees of PT Bagong Sangatta. The sampling technique used simple random sampling and obtained a sample of 67 respondents. Then analyzed using SPSS 26 with multiple linear regression analysis method. Leadership style and compensation have a significant and significant effect on employee performance. Implications Can provide information and suggestions for companies in improving employee performance by paying attention to leadership style and compensation at PT Bagong Sangatta and as a basis for further research. Originality Research with this title for the first time at PT Bagong Sangatta. The type of research is Empirical study